Ensino da arte na educação municipal de Uberlândia: potencialidades e silenciamentos no campo do multiculturalismo - Sá, Raquel Mello Salimeno de (2007)
This work retakes the development of art teaching in the education net of Uberlândia, state of Minas Gerais, between 1990 and 2006, aiming to identify potentialities and omissions in the multiculturalism field. It highlights how public policies have dealt with cultural matters in art education, how they are being put into practice in institutions that offer continuing teacher education programs and what they propose. It focuses on history, epistemology, and pedagogy in an attempt of articulating social, professional experience with art teaching and fostering a dialogue with different authors who deal with social, aesthetic theories and their relationship with art teaching in modernity and post modernity. It deals more deeply with conceptual assumptions related to the power relationships in education and their links with multiculturalism in art teaching. In so doing, it converges to sociology, anthropology and touches the paradigm crisis and their relationships with cultures, powers, and identities. It also makes some historical appointments on art education from its beginnings to its more relevant marks and points out the public policies action during different stages of capitalism from the institutionalization of art teaching to the current days to support the identification of advances and limitations in such policies in local and national art education; it considers that the inter-institutional relationships net defines advances and limitations related to the multiculturalism forms generated so far and which build themselves based on the notions of art, education, and culture. The investigation focus is the main centers of continuing education places aimed at teachers linked to the Universidade Federal de Uberlândia and to the Uberlândia city hall. It is guided by a dialogue between different methodological approaches combined with qualitative research procedures, with analysis of sources and records and with thematic oral history through interviews. The autobiographical method applied to me as a researcher and the oral history method applied to the research subjects were developed in the perspective of socials narratives. Therefore, one has searched to achieve the research aims and present a final, reflexive synthesis of the whole work.